IFN Regulatory Factor 1 Mediates Macrophage Pyroptosis Induced by Oxidized Low-Density Lipoprotein in Patients with Acute Coronary Syndrome - Guo, Min; Yan, Rui; Yao, Hongmei; Duan, Liqin; Sun, Meng; Xue, Zheng; Jia, Yongping (Mediators of Inflammation, 2019)
Background. Atherosclerosis (AS) is recognized as a chronic inflammatory disease. It is caused by the interaction between inflammatory cells such as macrophages, dendritic cells, and lipoproteins. Evidence has revealed that macrophage pyroptosis in lesion contributes to the formation of the necrotic core and thinning of the fibrous cap, which plays crucial roles in the onset of acute coronary syndrome (ACS). IFN regulatory factor 1 (IRF-1) is a pleiotropic transcription factor involved in various immune processes and cell death. We propose that IRF-1 may be implicated in macrophage pyroptosis in the pathogenesis of AS and ACS. Methods. Patients with stable angina, unstable angina, acute myocardial infarction, and clinical presentation of chest pain were enrolled. The expression of IRF-1 in human PBMC-derived macrophages was analyzed. Then, overexpression and inhibition of IRF-1 was performed in macrophages from patients with ACS to explore the possible role and mechanism of IRF-1 involvement in macrophage pyroptosis. Results. The expression of IRF-1 in macrophages was upregulated in ACS patients. The overexpression or inhibition of IRF-1 effectively modulated caspase-1 activation, as well as macrophage lysis, expression of gasdermin D-N (GSDMD-N), production of IL-1β and IL-18, and activation of NLRP3-ASC inflammasome, which were all inhibited by caspase-1 inhibitor. Further experiments revealed that pyroptosis and the downstream inflammatory response in AS induced by IRF-1 is a process that is dependent on reactive oxygen species (ROS) generation. Conclusion. Our observations suggest that IRF-1 potently activates ox-LDL-induced macrophage pyroptosis and may play an important role in AS and ACS.